Comparison of of Interleukin 23 Level in Gingival Crevicular Fluid between Peri-implantitis and Healthy Patients - Vahid Esfahanian; Shirin Zahra Farhad; Mohammad Bakhtiari; Mona Feyzollahi Almaloo (Mashhad University of Medical Sciences, 2018)
Introduction: Peri-implantitis is characterized by irreversible lesions that are caused by microbial plaque, involving not only the soft tissue around the implant, but also the implant-supporting bone. In the peri-implant diseases, some cytokines are increased, and inflammatory mediators, which are observed in peri-implantitis, induce the activation of osteoclasts and bone resorption. The aim of this study was to compare the level of interleukin 23 (IL-23) in patients with peri-implantitis and those with healthy peri-implant tissue. Materials & methods: This clinical trial was conducted on 19 patients with peri-implantitis and 19 patients with healthy peri-implant tissue. The samples were collected from sulcular fluid/gingival pocket fluid by paper cone and placed in vials. The level of IL-23 was determined using ELISA reader. Furthermore, the relationship of IL-23 levels with bleeding, probing depth, and pus formation was analyzed. Data analysis was performed using independent t-test, Pearson correlation coefficient, and Spearman test. Results: According to the results, the level of IL-23 in the patients with peri-implantitis was significantly higher than that in the group with healthy peri-implant tissue (P